A história da psiquiatria não contada por Foucault The History of the Psychiatry not told by Foucault - Fernando Ferreira Pinto de Freitas (História, Ciências, Saúde: Manguinhos, 2004)
O artigo propõe uma revisão da abordagem da loucura e do nascimento da instituição psiquiátrica proposta por Foucault em História da loucura. A hipótese desenvolvida é de que as origens da psiquiatria moderna revolucionam a perspectiva de abordagem da loucura, ao propor ser possível dialogar com o insensato, porque o louco não é aquele que perdeu a razão. Espera-se que a crítica à obra de Foucault em questão contribua para o processo de reforma psiquiátrica em curso no Brasil. The article proposes a revision of the approach to madness and the birth of the psychiatric institution taken by Foucault in History of Madness. The hypothesis is that the origins of modern psychiatry revolutionize the approach to madness by proposing it is possible to dialogue with the insane, because the madman is not someone who has lost his reason. It is hoped that this critique of Foucault's book will be a contribution to the process of psychiatric reform currently underway in Brazil.